Vascular endothelial growth factor: a neurovascular target in neurological diseases - Lange, Christian; Storkebaum, Erik; Ruiz de Almodóvar, Carmen; Dewerchin, Mieke; Carmeliet, Peter (Nature reviews. Neurology, 2016)
Vascular endothelial growth factor (VEGF) has been implicated in the aetiology and treatment of various neurological diseasesVEGF exerts effects on multiple cell types in the nervous system, including endothelial cells, neurons, astrocytes, microglia, oligodendrocytes and Schwann cellsVEGF protects neurons and fosters neurogenesis, and reduced VEGF levels contribute to neurodegenerative disordersVEGF can improve brain perfusion, partly by promoting angiogenesis, but pathological VEGF levels induce blood-brain barrier breakdown and vessel leakagePreclinical studies indicate that VEGF administration is beneficial in neurodegenerative diseases, peripheral neuropathies and epilepsyVEGF inhibition is approved as a treatment for neovascular ocular diseases, and might be beneficial in other neurological disorders involving BBB breakdown or excessive angiogenesis
Gesehen am 12.06.2020